2014
DOI: 10.1111/mec.13008
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of Afrocanarian blue tits inferred from genomewide SNPs

Abstract: A common challenge in phylogenetic reconstruction is to find enough suitable genomic markers to reliably trace splitting events with short internodes. Here, we present phylogenetic analyses based on genomewide single-nucleotide polymorphisms (SNPs) of an enigmatic avian radiation, the subspecies complex of Afrocanarian blue tits (Cyanistes teneriffae). The two sister species, the Eurasian blue tit (Cyanistes caeruleus) and the azure tit (Cyanistes cyanus), constituted the out-group. We generated a large data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…It should also be noted that, while diverged sperm morphology between species does not appear to indicate an inability of sperm to function in a heterospecific female environment, sperm morphological divergence can provide insight into the historical levels of gene flow between species (Gohli et al. ). That is, sperm morphology has a strong genetic basis (Mossman et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that, while diverged sperm morphology between species does not appear to indicate an inability of sperm to function in a heterospecific female environment, sperm morphological divergence can provide insight into the historical levels of gene flow between species (Gohli et al. ). That is, sperm morphology has a strong genetic basis (Mossman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Postcopulatory prezygotic barriers, and particularly reproductive proteins, evolve quite rapidly in other systems (Pitnick et al 2003;Dorus et al 2004;Ramm et al 2009). It should also be noted that, while diverged sperm morphology between species does not appear to indicate an inability of sperm to function in a heterospecific female environment, sperm morphological divergence can provide insight into the historical levels of gene flow between species (Gohli et al 2015). That is, sperm morphology has a strong genetic basis (Mossman et al 2009), so if there had been high levels of interbreeding between our taxa in the recent past, we might expect populations to have similar, rather than diverged, sperm morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The oldest and the closest island to the mainland (Fuerteventura) is only 100 km from the African (Moroccan) coast (Fernandez‐Palacios & Whittaker, 2008). Population genetic studies have demonstrated that the majority of taxa in the Canary Islands have a continental origin (Juan et al., 2000; Valente et al., 2017) and some species even show multiple waves of colonizations from the mainland (Gohli et al., 2015). The known genetic isolation levels of the bird populations in the Canary Islands compared to the mainland (Valente et al., 2017) allowed us to investigate in more detail the relationship between genetic isolation of host populations and haemosporidian infections.…”
Section: Methodsmentioning
confidence: 99%
“…Their distances to the adjacent continental mainland vary from 110 km (Fuerteventura in Canary Islands to Morocco) to more than 2000 km (Flores in the Azores to Portugal). Several colonization pathways have been identified (Juan et al, 2000; Emerson 2002; Emerson and Kolm 2005), including a single colonization event followed by stepping-stone dispersal (Juan et al, 1997; Emerson and Oromi 2005; Illera et al, 2007; Arnedo et al, 2008; Dimitrov et al, 2008), or multiple independent colonization events within the Canary Islands (Nogales et al, 1998; Ribera et al, 2003a; Díaz-Pérez et al, 2012; Rutschmann et al, 2014; Gohli et al, 2015; Stervander et al, 2015; Faria et al, 2016). While much research has been carried out on island evolution and endemism of terrestrial organisms, comparatively limited information exists for aquatic invertebrates (e.g.…”
Section: Introductionmentioning
confidence: 99%